EFFICACY OF ROSUVASTATIN IN DYSLIPIDEMIA CORRECTION IN PATIENTS AFTER Q-WAVE MYOCARDIAL INFARCTION - R. D. Kurbanov; N. U. Zakirov; Y. G. Kevorkova; N. B. Sayfiddinova (Столичная издательская компания, 2015)
Aim. To study the efficacy of rosuvastatin in dyslipidemia correction in patients after Q-wave myocardial infarction (Q-MI). Material and methods. 40 patients (aged 52.7±9.4 years old) were included into the study after 10-14 days of the acute Q-MI onset. Determination of blood lipids profile, alanine and asparagine transaminase levels was included into the initial examination. Rosuvastatin in a fixed dose of 20 mg/day was prescribed to the patients as a part of the standard therapy. Depending on the dynamics of the investigated parameters the individual doses of rosuvastatin were adjusted from 10 to 40 mg/day after 1 month of therapy. Final evaluation of blood lipids profile and transaminase levels was performed in the next 2 months of therapy. Results. Rosuvastatin 20 mg/day for 1 month in patients with an acute Q-MI provides a significant decrease in low-density lipoprotein (LDL) cholesterol level by 21.4%, and achievement of target levels of this parameter in 59.5% of patients. Rosuvastatin dose adjustment was required in 48.6% of patients after 1 month of therapy. Individually adjusted rosuvastatin doses provided the achievement of LDL cholesterol target levels by the end of the third month of treatment in 91% of patients. Elevated liver transaminase levels were observed in 7.5% of patients after 1 month of treatment. There were no new cases of adverse events after 3 months of therapy. Conclusion. Rosuvastatin 10-40 mg/day is effective and safe medicine for the treatment of dyslipidemia in patients after acute Q-MI.